Research works by UMP received recognition in Korea - Hardyana, Mohd.Saman (2018)
Research works by Universiti Malaysia Pahang (UMP) lecturers continued to receive recognitions following their wins of three gold medals, two special awards, one silver medal and four bronze medals at the Seoul Invention and International Fair (SIIF).